Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1101/337402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced Synthesis of Poly Gamma Glutamic Acid by Increasing the Intracellular Reactive Oxygen Species in the Bacillus licheniformis Δ1-pyrroline-5-carboxylate Dehydrogenase Gene ycgN Deficient Strain

Abstract: 35Importance γ-PGA is an anionic polyamide with various applications in biomedical and industrial fields. 36Proline metabolism influences the intracellular reactive oxygen species (ROS) and is involved in a wide 37 range of cellular processes. Here, we report the effects of proline metabolism on γ-PGA synthesis. Our

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The procedure of qRT-PCR was performed as described before. 40 The specific primers used for qRT-PCR are presented in Table S2. The 16 s rRNA gene was used as the internal standard to normalize the gene expression.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure of qRT-PCR was performed as described before. 40 The specific primers used for qRT-PCR are presented in Table S2. The 16 s rRNA gene was used as the internal standard to normalize the gene expression.…”
Section: Methodsmentioning
confidence: 99%
“…Li et al revealed that the overexpression of the gene ycgM (encoding proline dehydrogenase) and ycgN (encoding Δ 1 -pyrroline-5carboxylate dehydrogenase) decreases the production of γ-PGA by B. licheniformis WX-02 by disturbing the intrinsic reactive oxygen species level. 40 In contrast to B. licheniformis WX-02, overexpression of both putM (encoding proline dehydrogenase) and rocA (encoding Δ 1 -pyrroline-5-carboxylate dehydrogenase) increased γ-PGA production in B.…”
Section: Enhancement Of the Pppmentioning
confidence: 99%
“…1). In the previous research, knocking out of P5CDH encoded gene Ldp5cdh in the Colorado potato beetle Leptinotarsa decemlineata could significantly reduce the ATP content, and further inhibit flight capacity (42). This study implied that deletion of ycgN in B. licheniformis WX-02 led to an 85.22% increase of γ-PGA yield.…”
Section: Discussionmentioning
confidence: 60%
“…Proline is a multifunctional amino acid which can be used as carbon, nitrogen and energy source (18). Also, it plays an important role in protecting against osmotic and oxidative stresses, since it is a compatible solute and a free-radical scavenger (42). In addition, proline catabolism has been found to be involved in protection of intracellular redox homeostasis and virulence in microorganisms (26,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation